A Novel RAB33B Mutation in Smith–McCort Dysplasia. Issue 2 (8th November 2012) - Dupuis, Nina; Lebon, Sophie; Kumar, Manoj; Drunat, Séverine; Graul‐Neumann, Luitgard M.; Gressens, Pierre; El Ghouzzi, Vincent
<x xml:space="preserve">Abstract</x> Smith‐McCort dysplasia is a disorder with skeletal features identical to those of Dyggve‐Melchior‐Clausen syndrome but with normal intelligence and no microcephaly. Although both are associated with mutations in the Golgi protein DYMECLIN, genetic heterogeneity has been suspected for SMC. The study describes an SMC patient with a loss‐of‐function mutation in the GTP‐binding domain of RAB33B, which is involved in Golgi trafficking. These data confirm the genetic heterogeneity of SMC and highlight the role of Golgi transport in the pathogenesis of SMC/DMC. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>